2022
DOI: 10.1128/mbio.01239-22
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase (PI3K) Orchestrates Aspergillus fumigatus-Induced Eosinophil Activation Independently of Canonical Toll-Like Receptor (TLR)/C-Type-Lectin Receptor (CLR) Signaling

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is caused by the fungus Aspergillus fumigatus , afflicts about five million patients globally, and is still a noncurable disease. ABPA is associated with pronounced lung eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…We found that E_C3/E_C4 clusters could recruit TAM_GPNMB through the ligand‒receptor pairs CCL3/CCL4-CCR3 (Fig. 7A ) [ 55 ]. Moreover, with the expression of TGF-β family genes, including TGFB1, TGFB3 and HBEGF, these two subclusters could induce the involvement of TAM_GPNMB in extracellular matrix remodelling, thereby promoting the migration of KCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that E_C3/E_C4 clusters could recruit TAM_GPNMB through the ligand‒receptor pairs CCL3/CCL4-CCR3 (Fig. 7A ) [ 55 ]. Moreover, with the expression of TGF-β family genes, including TGFB1, TGFB3 and HBEGF, these two subclusters could induce the involvement of TAM_GPNMB in extracellular matrix remodelling, thereby promoting the migration of KCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, expression of L-selectin (CD62L), a neutrophil marker of adhesion to endothelial cells and migration ( 53 ), was increased in response to supernatants of infected VECs and lower in the presence of anti-candidalysin nanobodies. CD62L is expected to be inversely regulated with CD11b during granulocyte activation in vitro ( 54 56 ), since CD62L is rapidly shed during activation ( 53 ). It is, therefore, difficult to determine how the increased CD62L surface expression, which was reduced by the nanobodies, reflects neutrophil activation state.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent unspecific staining, neutrophils were pre-incubated with Fc-Block Human TruStain FcX (BioLegend) before adding a mix of fluorophore-linked antibodies against the following activation status indicating surface molecules: CD11b-BV421 (ICR44), CD15-APC-Fire750 (W6D3), CD16-PerCP-Cy5.5 (3G8), CD35-FITC (E11), CD62L-AlexaFluor647 (DREG-56), CD66b-PE (G10F5), and CD182-PE-Cy7 (5E8, all from BioLegend). Activation markers were selected based on previous observations of granulocyte responses to fungal pathogens or associated stimuli ( 52 , 54 , 57 ). Fixable Viability Dye eFluor506 (Invitrogen) was used to exclude dead cells.…”
Section: Methodsmentioning
confidence: 99%